Altajg sahigč zahčin arduud ugsaatny tuhaj tüüh XVIII - XX zuuny ėhėn üe - Tamir, Šaraagijn (Soëmbo printing, 2020)
XVIII - XX century history account of the Zakhchin people, a subgroup of the Oirats mainly residing in Khovd province, Mongolia